Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.apsusc.2021.149217
|View full text |Cite
|
Sign up to set email alerts
|

Mapping surface segregation of single-atom Pt dispersed in M surfaces (M = Cu, Ag, Au, Ni, Pd, Co, Rh and Ir) under hydrogen pressure at various temperatures

Abstract: Single-atom alloys (SAAs) are emerging materials containing isolated metal atoms dispersed on host metal surfaces, exhibiting unique reactivity compared with the corresponding monometallic counterparts. However, the stability of the isolated atoms in the host metal has hardly been studied, although, metal segregation has been commonly observed in bimetallic nanoparticles under reaction conditions. In this work we focus on single-atom Pt anchored on various metallic support surfaces. Density Functional Theory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The SOE of H­(ads) is however more favorable on the PdCu SAA than on the PdAu SAA, resulting in the former being better than the latter as a hydrogenation catalyst . Spectator species with large SOEs have also been shown to modulate the performance of SAA catalysts, with CO­(ads) or I­(ads) being prominent examples of these effects, , or even to stabilize SAA surfaces by anchoring dopants at the surface of the catalyst. , Therefore, the ability to understand factors affecting the SOEs and predict SOEs for a wide range of chemical intermediates on various SAA surfaces is key to the development of this new class of catalysts.…”
mentioning
confidence: 99%
“…The SOE of H­(ads) is however more favorable on the PdCu SAA than on the PdAu SAA, resulting in the former being better than the latter as a hydrogenation catalyst . Spectator species with large SOEs have also been shown to modulate the performance of SAA catalysts, with CO­(ads) or I­(ads) being prominent examples of these effects, , or even to stabilize SAA surfaces by anchoring dopants at the surface of the catalyst. , Therefore, the ability to understand factors affecting the SOEs and predict SOEs for a wide range of chemical intermediates on various SAA surfaces is key to the development of this new class of catalysts.…”
mentioning
confidence: 99%
“…Experimental and theoretical studies agree that for Ir–Au nanoparticle segregation is energetically favored over mixing. ,,, It was also found that these bimetallic nanoparticles exhibit a surface structure that is much closer to (100) than to (111) surfaces . In order to emulate the structure of these nanoparticles, we focus our study on Ir, Au, and Ir–Au (100) surfaces.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…It is important to keep in mind that, especially at high temperatures, NPs are dynamic materials: dopants can migrate within the surface and between the surface and the bulk. During the preparation of the catalyst or under the operating conditions, adsorbates can strongly affect the stability of SAAs . Accounting for the adsorbate spillover energy is therefore crucial to constructing a good model of the surface state of the NP under the experimental conditions. ,, The study of such effects is ongoing, but some interesting results have already been demonstrated.…”
Section: Adsorption On Single-atom Alloysmentioning
confidence: 99%